Analysis of gene expression profiles under water stress in tolerant and sensitive sugarcane plants - Rodrigues, Fabiana Aparecida [UNESP]; de Laia, Marcelo Luiz [UNESP]; Zingaretti, Sonia Marli [UNESP] (Elsevier B.V., 2009)
Water stress decreases plant productivity. To detect genes expressed under drought conditions, we performed a gene expression study using drought tolerant (SP83-5073) and sensitive (SP90-1638) sugarcane plants. Gene expression profiles were monitored by macroarray membranes containing 3575 cDNA clones from sugarcane leaf libraries, and the results were confirmed by real time PCR analysis. In the tolerant cultivar, we identified 165 genes that were expressed in response to water stress, in contrast with the sensitive cultivar, in which a higher number of genes (n = 432) were responsive to the stress treatment. The number of expressed genes in the sensitive cultivar increased with the severity of water deficit. In despite few genes had been differentially expressed in tolerant plants, 94% of them were up-regulated by stress, while 45% of the genes expressed in sensitive plants were down-regulated under water stress conditions. Comparing the gene expression profiles verified 91 common genes between both cultivars, the majority of which were up-regulated by water deficit. Genes were organized according to roles in cellular metabolism. Important stress-related pathways were repressed in sensitive plants. In both cultivars, we observed a great number of unknown genes, which will provide news insights in water deficit tolerance studies. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Water stress; Transcriptome; Macroarray; Gene expression; Sugarcane